The Effect of Anterior Segment Depth on the Accuracy of 7 Different Intraocular Lens Calculation Formulas - Cem Kesim; Ayşe Yıldız-Taş; Melisa Zişan Karslıoğlu; Murat Hasanreisoğlu; Orkun Müftüoğlu; Afsun Şahin (Türk Oftalmoloji Dergisi, 2022)

(untitled)
Objectives:To evaluate the effect of anterior segment depth (ASD; sum of anterior chamber depth and lens thickness) on the accuracy of 7 intraocular lens formulas calculated in patients with axial length (AL) between 22.5 and 24.5 mm.Materials and Methods:In this retrospective study, patients who underwent cataract surgery were divided into three groups based on their ASD measurements (Group I: ASD <7.30 mm, Group II: ASD between 7.30-7.90 mm, Group III: ASD >7.90 mm). The mean predictive error (MPE), mean absolute error (MAE), and median absolute error (MedAE) values of each group were compared. The effect of ASD on the predictive error (PE) of each lens formula was additionally tested in subgroups based on mean keratometry (K) values (Subgroup I: K <42.0 D, Subgroup II: K between 42.0-44.5 D, Subgroup III: K >44.5 D).Results:The study included 184 eyes of 184 patients. In Group I, all formulas except Olsen OLCR and Barrett II had clinically myopic MPEs. In Group II, the MPEs of all lens formulas except Barrett II were statistically non-different from zero (p>0.05). In Group III, the MPEs of all lens formulas were found to be statistically hyperopic. In Group III, all formulas except Olsen OLCR were significantly shifted to more hyperopic results when compared with Groups I and II (p<0.05). ASD was positively correlated with the PEs of the SRK/T, Holladay I, Hoffer Q, Barrett II, Hill-RBF, and Haigis formulas. In cases with mean K greater than 42.0 D, ASD was similarly correlated with PE for all formulas except Olsen OLCR.Conclusion:In eyes with AL between 22.5 and 24.5 mm, the predictions of lens formulas were significantly hyperopic in cases with greater ASD.